Pengaruh Gaya Kepemimpinan, Disiplin, Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai UPT Puskesmas Kecamatan Sluke Kabupaten Rembang - Anisatul Hisan; Anik Nurhidayati (Universitas Batanghari Jambi, 2023)
The purpose of the research was to show the influence of leadership style, discipline, motivation, and work environment on the performance of UPT Puskesmas employees. With a population of 68 UPT Puskesmas officers in Sluke District and Rembang Regency. A way to collect data through questionnaires. Saturated samples are used in the sampling procedure. The data analysis method uses multiple linear regression. The results of the study showed that the leadership style variable had a significant positive effect but was not statistically significant on employee performance, work discipline variable had a significant positive effect on employee performance and work motivation variable had a significant positive effect on employee performance